Gubernatorzy wojskowi w systemie polskiej administracji początków XIX wieku. - Marszałek, Piotr Krzysztof (Wydawnictwo Poznańskie sp. z o.o., 2012)
In Polish literature on the subject, the military governor’s office is usually associated with the organisation of the administrative system that prevailed in the partitioning states (Poland’s Partitions 1791-1918). However, the governor’s office had already been known in Poland during the Duchy of Warsaw (1807-1815), when it was, like many other solutions of administrative and military law, imported directly from France. In the structure of Polish public organs, the office of governor was created for the first time during the Polish-Austrian war in 1809. Although no documents have survived from which we could learn of the competences of a Polish governor in those times, what is known is that the description of his authority followed closely the model set out by the French legislation. It was not before the Polish-Russian war in 1830-1831 that first attempts were made to independently set out the authority of a governor of the Polish state, but even then, at least initially, the solutions set forth by the regime of the Napoleonic decree were directly referred to and copied. In the second half of the 19th century, shortly before the collapse of the November Uprising, a draft describing the office and competences of a Polish governor was finally ready to be put forward for parliamentary discussion, but it was already too late for the Sejm to deal with it.

Dans la littérature polonaise, la fonction du gouverneur militaire est associée parfois à l’organisation administrative des États envahisseurs de l’époque. Cependant, cette fonction est connue et elle existe dans la structure des autorités polonaises sous le Duché de Varsovie. À l’époque, ses exemples nous viennent de France, comme d’ailleurs la plupart des solutions en matière de l’administration, du droit militaire et de la guerre. La fonction apparaît pour la première fois dans la structure des pouvoirs publics polonais pendant la guerre polono-autrichienne en 1809. Nous manquons cependant de documents déterminant les compétences de la fonction. Toutefois, nous savons qu’à l’époque sont appliquées strictement les mêmes solutions que celles de la législation française en vigueur. Les tentatives de définir individuellement les compétences de la fonction de gouverneur militaire n’apparaissent que pendant la guerre polono-russe dans les années 1830-31. Mais même le cas échéant, d’abord, on se référait directement aux solutions déterminées par le régime du décret napoléonien de 1811. Et c’est seulement vers la dernière période de l’Insurrection de Novembre, que le gouvernement commence à définir l’étendue du pouvoir de gouverneur. Le projet en application a même été préparé pour la Diète [chambre basse du parlement polonais, NDT]. Hélas, cette dernière n’a plus eu le temps de le traiter.
Keywords: administracja; gubernator wojskowy; XIX wiek; Królestwo Polskie